Assessment of Blood Lead Levels and Associated Risk Factors Among Children in Ulaanbaatar, Mongolia - L Praamsma, Meredith; Ganbaatar, Nasantogtokh; Tsogtbaatar, Munkhtsetseg; Halmambetova, Elnura; Malchinkhuu, Enkhzol; Ochir, Chimedsuren; Ulziibayar, Ganchimeg; Olkhanud, Purevdorj B (Central Asian Journal of Medical Sciences, 2016)
Objectives: The objectives of this study were to determine BLLs with a LeadCare II analyzer in children living in Ulaanbaatar, Mongolia and to identify potential risk factors influencing their BLLs with a lifestyle and residential environment questionnaire. Methods: A total of 153 children aged 6-8 years old were tested in 2014. Results: The geometric mean BLL was 5.3 µg/dL (95% CI: 4.9 – 5.7 µg/dL) and 69.3% of the children had blood lead levels ≥5 μg/dL (the United States Centers for Disease Control and Prevention’s current reference level). Factors that were significant (p<0.05) predictors of BLL in a multiple linear regression model were sex, age, father’s education level, and father’s job type. The BLL from this study in 2014 shows a 60% decrease since a prior 2005 study, likely due to the ban on leaded gasoline in the country. Conclusion: Academic performance was significantly influenced by BLL, indicating that actions still need to be taken to reduce lead exposure in Ulaanbaatar.